Está en la página 1de 4

Arkansas Tech University

MATH 1203: Trigonometry


Dr. Marcel B. Finan
21 Conversion Identities
In this section, you will learn (1) how to restate a product of two trigono-
metric functions as a sum, (2) how to restate a sum of two trigonometric
functions as a product, and (3) how to write a sum of two trigonometric
functions as a single function.
Product-To-Sum Identities
By the addition and subtraction formulas for the cosine, we have
cos (x + y) = cos x cos y sin x sin y (1)
and
cos (x y) = cos x cos y + sin x sin y. (2)
Adding these equations together to obtain
2 cos x cos y = cos (x + y) + cos (x y) (3)
or
cos x cos y =
1
2
[cos (x + y) + cos (x y)] (4)
Subtracting( 1) from ( 2) to obtain
2 sin x sin y = cos (x y) cos (x + y) (5)
or
sin x sin y =
1
2
[cos (x y) cos (x + y)]. (6)
Now, by the addition and subtraction formulas for the sine, we have
sin (x + y) = sin x cos y + cos x sin y
sin (x y) = sin x cos y cos x sin y.
1
Adding these equations together to obtain
2 sin x cos y = sin (x + y) + sin (x y) (7)
or
sin x cos y =
1
2
[sin (x + y) + sin (x y)]. (8)
Identities ( 4), ( 6), and ( 8) are known as the product-to-sum identities.
Example 21.1
Write sin 3x cos x as a sum/dierence containing only sines and cosines.
Solution.
Using ( 8) we obtain
sin 3x cos x =
1
2
[sin (3x + x) + sin (3x x)]
=
1
2
(sin 4x + sin 2x)
Sum-to-Product Identities
We next derive the so-called sum-to-product identities. For this purpose,
we let = x + y and = x y. Solving for x and y in terms of and we
nd
x =
+
2
and y =

2
.
By identity ( 3) we nd
cos + cos = 2 cos (
+
2
) cos (

2
). (9)
Using identity ( 5) we nd
cos cos = 2 sin (
+
2
) sin (

2
). (10)
Now, by identity ( 7) we have
sin + sin = 2 sin (
+
2
) cos (

2
). (11)
2
Using this last identity by replacing by and using the fact that the sine
function is odd we nd
sin sin = 2 sin (

2
) cos (
+
2
). (12)
Formulas (9) - (12) are known as the sum-to-product formulas.
Example 21.2
Establish the identity:
cos 2x+cos 2y
cos 2xcos 2y
= cot (x + y) cot (x y).
Solution.
Using the product-to-sum identities we nd
cos 2x + cos 2y
cos 2x cos 2y
=
2 cos (
2x+2y
2
) cos (
2x2y
2
)
2 sin (
2x+2y
2
) sin (
2x2y
2
)
=cot (x + y) cot (x y)
Writing a sin x + b cos x in the Form k sin (x + ).
Let P(a, b) be a coordinate point in the plane and let be the angle with
initial side the x-axis and terminal side the ray

OP as shown in Figure 21.1


Figure 21.1
Let k =

a
2
+ b
2
. Then, according to Figure 91 we have
cos =
a

a
2
+ b
2
and sin =
b

a
2
+ b
2
.
3
Then in terms of k and we can write
a sin x + b cos x =

a
2
+ b
2

a
2
+ b
2
sin x +
b

a
2
+ b
2
cos x

=k(cos sin x + sin cos x) = k sin (x + ).


Example 21.3
Write y =
1
2
sin x
1
2
cos x in the form y = k sin (x + ).
Solution.
Since a =
1
2
and b =
1
2
we nd k =

(
1
2
)
2
+ (
1
2
)
2
=

2
2
, cos =
a
k
=

2
2
, sin =
b
k
=

2
2
. Thus = 45

and
y =

2
2
sin (x 45

).
4